Piezoelectric actuators and generators for energy harvesting : research and development /: research and development. ([2018]) - Shevtsov, Sergey N; Soloviev, Arkady N; Parinov, Ivan A; Cherpakov, Alexander V; Chebanenko, Valery A
No abstract available